A historical exposition on the fundamental features of the federal constitution and its importance to judicial interpretation: a study on Article 121(1A) - Ishak, Badruzzaman; Ab Aziz, Shamrahayu (IIUM Press, 2022)
The FederalConstitution haslastedformore thanhalf a centuryafter its introduction. Recent developmentshavewitnessed various constitutional issues, some of themwerecontroversial in naturesuch as the latest interpretation of Article 121 (1A) by the judiciary.Hence, an exposition on the heritage foundation of the Constitution is crucial in addressing thesedevelopments. The judiciary needs to understand the spirit of all constitutional provisions in order to achieve the correct interpretation of theintention of the legislator. Each country frames its constitution according to its own history and for the good of its own society. The objective of the article is to highlight certain customary elements which form the fundamental features of the Federal Constitution especially on the position of Islam as the religion of the Federation.The research methodology adopted in this article is a doctrinal analysis on the historical narrative that is meant to unearth certain aspects of the fundamental features of the Federal Constitution. The article also analyses the past and recent cases where the judiciary hadcome upwith different interpretationsof Article 121 (1A)